(untitled) (Herald of Journalism, 2018)
Migration processes are very relevant for Kazakhstan. The imbalance of development between the countries of the region; the transit component of the territory of Kazakhstan; the complex interethnic composition of countries contribute to the permanent control of the migration policy of the republics. Most often, labor migrants are called “guest workers”, the term has an ironic character. Migrants are people forced to come to work because of a difficult economic situation. In this connection, the public of the host country has a contemptuous attitude towards “guest-workers” as to the spreaders of the “contagion”, instigators of the criminal situation and other stereotypes. The task of the media is to ensure proper public perception of migration issues: an understanding of the global nature of this topic, an objective assessment of migration processes, a “normal” image of a migrant, etc. In modern publications, the idea of “we” is rather emphasized. And in this case, journalists benefit from the idea of “their” and “others” to attract the audience. According to researchers of this topic, the 198 Вестник. Серия журналистики. №1 (47). 2018 Освещение миграционных процессов и образ мигранта в СМИ image of a migrant in the media is a multi-stage design, consisting of personal and editorial settings, stereotypes, oppositions, verbal aggression, etc. The analysis of the publication in the mass media and social networks of Kazakhstan allows us to divide the problems of the migration process into themes: crime, international conflicts, interethnic / international marriages. The role and responsibility of the media in regulating migration processes is to explain the laws and regulations of labor migration and emigration, to inform objectively about migration processes and events related to it, to create a “normal” image of the migrant. Key words: migration, migrants, mass media, responsibility of the media.